La-doped WO3@gCN Nanocomposite for Efficient degradation of cationic dyes. Issue 10 (15th May 2023) - Shaheen, Nusrat; Warsi, Muhammad Farooq; Zulfiqar, Sonia; Althakafy, Jalal T.; Alanazi, Abdullah K.; Din, Muhammad Imran; Abo-Dief, Hala M.; Shahid, Muhammad
Abstract: In present investigation, gCN supported carbon coated Lanthanum doped tungsten oxide (C@LWO/gCN) composite were synthesized via hydrothermal approach. The photodegradation of different cationic dyes like malachite green (MG), crystal violet (CV) and methylene blue (MB) has been carried out under prepared C@LWO/gCN composite. Furthermore, the comparative photodegradation was also performed using pristine LWO and C@LWO nanowires. The synthesized samples were characterized via physiochemical techniques such as XRD, FESEM, EDX, FTIR, BET and UV/Vis spectroscopy. The results proved incorporation of La ions into WO3 lattice and reduced band gap of doped sample which significantly boost up the capability of the material towards photodegradation. The maximum degradation was found out at pH = 6, 5 mg catalyst dose, 5 ppm dye concentration and 35 °C temperature. The achieved results proved that the trapping agents compete with prepared composite specie for the h +, e −, HO ● and O2 ●- radicals. The obtained experimental records of photodegradation of cationic dyes using C@LWO/gCN composite has correlation with pseudo first order kinetics, Langmuir-Hinshelwood model and t1/2 . The simplest facile synthetic approach, remarkable photodegradation performance against colored and colorless effluents suggest that C@LWO/gCN composite exhibit great potential for large-scale wastewater treatment. Graphical abstract: Image 1